Estimativa da perda auditiva em neonatos nascidos em hospitais municipais de São Paulo - Stadulni, Andréia Rodrigues Parnoff (2013)
Introduction: After neonatal hearing screening became mandatory in Brazil, further scientific studies are relevant in order to draw a profile of the newborns diagnosed with hearing loss across the country. Purpose: To estimate hearing loss in infants born at municipal hospitals in São Paulo (SP), Brazil. Methods: Participants were 37,479 infants born at 11 municipal hospitals in São Paulo between October 2010 and October 2011, who resided in the Southeast, Midwest, North or South regions of the city. Subjects who failed the universal neonatal hearing screening (UNHS) were referred to hearing health reference centers for audiological diagnosis, and those with sensorineural hearing loss were genetically assessed. Results: From a total of 182,986 births in the city of São Paulo, 37,479 (20.48%) occurred at the 11 municipal hospitals considered and were selected for this study. Of all the newborns referred for audiological diagnosis (76/37,479=0.2%), 76.3% (58/76) concluded the diagnostic process, with a follow-up loss of 23.69%. From those who concluded the process, 50% presented normal results, 29.3% had conductive hearing loss, 19% had bilateral sensorineural hearing loss, and 1.7% presented unilateral sensorineural hearing loss. The estimated prevalence of hearing loss is 0.10%, with a 95% confidence interval given by [0.07%; 0.14%]. From the subjects who were genetically assessed 5 (55.5%) did not present 35delG mutation, 2 (22.2%) are still under investigation for syndromes (including one for Waardenburg and one for congenital hypothyroidism), 1 (11.15%) had probable hereditary hearing loss due to consanguineous parents, and 1 (11.15%) were homozygous for c.35delG mutation. Conclusion: The estimated hearing loss for the city of São Paulo, Brazil, is equivalent to those of developed countries